Análisis de servicios de virtualización de servidores en la nube. - Planta Ulloa, Jacqueline Patricia (2024)
Through this research case, virtualization services were analyzed of servers in different clouds; This system involves understanding the security that these software provide when storing data in a cloud, since it allows us to know the physical infrastructure of each server and the ability to expand operations efficiently through architecture and artificial intelligence. Allowing security stability in the computer data of said systems since they are stored through digital containers, where the virtualization services that they provide to the user in a flexible and fast manner are effectively supported, eliminating the migration of information. These services are used in various companies, being a strategy thorough comprehensive transition of virtualized data within the computer systems to be used; The objective of cloud servers is to facilitate remote work and collaboration between distributed teams of a well-developed computer system with a physical infrastructure, thus giving better implementation and management of data stored in the cloud and with each characteristic of the clouds. activities to be virtualized of said company, on a solid basis. Where the need for the benefits of migrations is analyzed information in the clouds, where virtualization simplifies the administrative management of the resources it uses, where it is stated that the clouds are part of a backup through an internet connection where it provides open source, with extensive support and a range optimized for systems on Linux, Windows and their various features; helping us with the performance and frequent use of virtual servers and cloud storage.